Knowledge in The Perspective of Islamic Religion: A Qualitative Study of The Thought of Imam Al-Ghazali Scholars - Annisah Safitri; Hafidz Hafidz; Chusniatun Chusniatun; Ahmad Akbar Fauzi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study Science from an Islamic perspective is not only understood as the result of rationality and scientific methods, but also includes moral, spiritual, and transcendental dimensions that are oriented towards the recognition and devotion to Allah SWT. The problem that arises in the development of modern science is the dichotomy between religious science and general science which has an impact on scientific fragmentation and value crisis in Islamic education. This article aims to examine the concept of science as well as the view of the integration of religious science and general science according to Imam Al-Ghazali as a criticism of the dichotomy of science. This study uses a literature study method with a qualitative approach, with primary data sources in the form of works of Imam Al-Ghazali such as Ihya' 'Ulum al-Din and Risalah al-Laduniyyah, as well as secondary data sources in the form of relevant books and scientific articles. The results of the study show that Imam Al-Ghazali views knowledge as a means of getting closer to Allah, which must be based on ethical and moral values. The division of knowledge into the categories of fardhu 'ain and fardhu kifayah as well as shari'iyyah and 'aqliyyah is not intended as a dichotomous separation, but as a functional classification based on its usefulness and priority for the life of the ummah. Al-Ghazali emphasized that religious science and general science are complementary to each other, where reason requires the guidance of revelation and revelation requires understanding of reason. Thus, Imam Al-Ghazali's thought affirms the importance of the integration of knowledge within the framework of monotheism as the foundation for the development of holistic Islamic science and education that is relevant to the challenges of the globalization era.